Given \( g(x) = 1 - x^{2} \), substitute \( x = 0 \): \[ g(0) = 1 - (0)^{2} = 1 - 0 = 1 \]
Now, substitute \( g(0) = 1 \) into \( f(x) = 8x - 4 \): \[ f(g(0)) = f(1) = 8(1) - 4 = 8 - 4 = 4 \]
Given \( f(x) = 8x - 4 \), substitute \( x = 0 \): \[ f(0) = 8(0) - 4 = 0 - 4 = -4 \]
Now, substitute \( f(0) = -4 \) into \( g(x) = 1 - x^{2} \): \[ g(f(0)) = g(-4) = 1 - (-4)^{2} = 1 - 16 = -15 \]
(a) \( f(g(0)) = \boxed{4} \)
(b) \( g(f(0)) = \boxed{-15} \)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.